2020
DOI: 10.1111/eci.13380
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness and microvascular disease in type 2 diabetes

Abstract: Background The clustering of arterial stiffness with microvascular disease (MD) and their effects on the clinical outcome of patients with type 2 diabetes (T2D) remains not fully clarified. Methods In a prospective study of 414 patients with T2D, we investigated the prognostic value of arterial stiffness and MD for clinical outcomes. Participants were assessed for the presence of MD (ie diabetic retinopathy, nephropathy and neuropathy) and arterial stiffness by pulse wave velocity (PWV) and followed‐up for a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…First, the AS-DR relationship is strongest with PDR type,[ 11 13 ] which was prevalent lesser than NPDR in the study. Second, we did not have baseline data as reported recently[ 21 ] that baseline PWV is not associated with microvascular dysfunction. The same could have happened in our participants as diagnosis of type 2 diabetes is late.…”
Section: Discussionmentioning
confidence: 98%
“…First, the AS-DR relationship is strongest with PDR type,[ 11 13 ] which was prevalent lesser than NPDR in the study. Second, we did not have baseline data as reported recently[ 21 ] that baseline PWV is not associated with microvascular dysfunction. The same could have happened in our participants as diagnosis of type 2 diabetes is late.…”
Section: Discussionmentioning
confidence: 98%
“…Angiogenesis is a prerequisite for the healing of skeletal conditions such as fractures and defects ( Maes, 2013 ; Ramasamy et al, 2016b ). Vascular injury is a major contributor to many organ dysfunctions caused by diabetes, which are referred to as diabetic vascular complications ( Beckman and Creager, 2016 ; Antonopoulos et al, 2021 ). Previous studies on diabetic bone vessels have focused on the relationship between vascular injury and abnormal hematopoiesis in the bone marrow, and little attention has been given to the potential association between the bone vascular system and bone mass lesions ( Fajardo, 2017 ; Shanbhogue et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy may be attributable to the race difference and stricter exclusion criteria in the present study, specifically with acute coronary syndrome, cerebrovascular disease, and peripheral arterial disease, which might influence the measurement of AS. Subgroup analysis from another study investigating the clustering of AS and microvascular complications of T2DM and their effects on the composite clinical endpoints found that PWV was correlated with neither the presence of microvascular complications at baseline nor its deterioration at follow-up [37]. The study defined microvascular complications as the presence of DR, diabetic kidney disease, and diabetic neuropathy or diabetic foot.…”
Section: Discussionmentioning
confidence: 99%